The new date, new format, new goals and new sponsor of the Archon Genomics X PRIZE Competition - Kedes, Larry; Campany, Grant (Nature genetics, 2011)
The Archon Genomics X Prize contest has been declared for January 2013. Larry Kedes and Grant Campany explain the selection of centenarian genomes for the contest and provide the rules by which the contestants will be judged.